Vertebral body tethering: An alternative to posterior spinal fusion in idiopathic scoliosis? - Hammad, Ahmad M.; Balsano, Massimo; Ahmad, Alaaeldin A. (Frontiers in Pediatrics, 2023)
Introduction Skeletally immature patient with adolescent idiopathic scoliosis (AIS) whose curves continue to progress despite bracing should be treated surgically. Vertebral body tethering (VBT) is a non-fusion, compression-based, growth preserving alternative to posterior spinal fusion (PSF) based on the concept of ‘growth modulation’ to prevent possible functional complications secondary to fusion while correcting scoliotic deformity. This review aims to shed light on the indications of VBT, short- and medium-term outcomes, describe the surgical technique and associated complications, and to compare its efficacy to that of PSF. Methods A review of peer-reviewed literature on VBT as a surgical technique, its indications, outcomes, complications, and comparison with other surgical interventions to correct AIS was conducted in December 2022. Results Indications remain controversial and mainly include stage of skeletal maturity based on radiographic markers, curve location, magnitude and flexibility, and presence of secondary curve. Assessment of VBT clinical success should not be restricted to improvement in radiographic parameters but should include functional results and patient-centered outcomes, improved body image and pain, and durability of outcomes. In contrast to fusion, VBT seems to be associated with preserved spinal growth, shorter recovery, potentially better functional outcomes, less motion loss but possibly less curve correction. Discussion Yet still, with VBT there exists a risk of overcorrection, construct breakage or failure of procedure which require revision and at times conversion to PSF. Patient and family preferences must be accounted for acknowledging gaps in knowledge, attributes and drawbacks of each intervention.